2017
DOI: 10.1038/nature22975
|View full text |Cite|
|
Sign up to set email alerts
|

Host and viral traits predict zoonotic spillover from mammals

Abstract: The majority of human emerging infectious diseases (EIDs) are zoonotic, with viruses originating in wild mammals of particular concern (e.g. HIV, Ebola, SARS)1–3. Understanding patterns of viral diversity in wildlife and determinants of successful cross-species transmission, or spillover, are therefore key goals for pandemic surveillance programs4. However, few analytical tools exist to identify which host species likely harbor the next human virus, or which viruses can cross species boundaries5–7. Here we con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

50
1,154
6
39

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 929 publications
(1,249 citation statements)
references
References 52 publications
50
1,154
6
39
Order By: Relevance
“…For instance, authors reported that "many zoonotic viruses that have emerged recently are thought to have their origins in bats" (Wang et al 2015) and that "many emerging and re-emerging infectious diseases are zoonoses derived from wildlife, particularly bats" (Wynne et al 2014). Although it has recently been found that bats host a significantly higher proportion of zoonoses than other mammals (Olival et al 2017), there are still only poor real-world data showing to which extent such diseases might jump from wildlife to humans (Kupferschmidt 2017). Moreover, direct associations of unrelated statements placed in proximity and missing critical information led to misleading conclusions.…”
Section: Bats Viruses and Framesmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, authors reported that "many zoonotic viruses that have emerged recently are thought to have their origins in bats" (Wang et al 2015) and that "many emerging and re-emerging infectious diseases are zoonoses derived from wildlife, particularly bats" (Wynne et al 2014). Although it has recently been found that bats host a significantly higher proportion of zoonoses than other mammals (Olival et al 2017), there are still only poor real-world data showing to which extent such diseases might jump from wildlife to humans (Kupferschmidt 2017). Moreover, direct associations of unrelated statements placed in proximity and missing critical information led to misleading conclusions.…”
Section: Bats Viruses and Framesmentioning
confidence: 99%
“…Although we acknowledge that bats may represent an important share of natural virus reservoirs (Anthony et al 2017, Maxmen 2017, Olival et al 2017) that might eventually pose danger to people, we remain firm in asserting that the risk of virus transmission from bats to humans is small (Kingston 2016, Anthony et al 2017, an aspect that is worryingly neglected in most virological bat-related publications. Moreover, the fact that an increasing number of virus outbreaks is largely attributable to human encroachment in natural areas (Buttke et al 2015, Terraube et al 2017) is rarely publicised.…”
Section: Bats Viruses and Framesmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, over eons, bats have evolved to cope with these challenges, often leading to survival despite viral exposure (for a comprehensive list of viruses detected in bats, see 54). Epidemiological studies and field surveys suggest viruses circulate in wild bat populations (12,55) without causing the great morbidity or mortality observed as a result of viral spillovers into humans (Table 1) (14,56). Although the processes through which bats manage to clear viral infections remain poorly understood, possible explanations for the resilience of individual bats to these infections include not only heightened immune function but modulation of inflammation and mechanisms of repair (16).…”
Section: Model For Enhanced Disease Resistancementioning
confidence: 99%
“…High-quality bat genomes (e.g., including regulatory regions) from diverse species are needed to determine both how extensive these interactions between bats and viruses have been and what innate genetic mechanisms bats use to clear these viruses. Coupled with viral monitoring in the wild and viral genomics, bat genomic analyses have the potential to predict and manage future spillover events (56).…”
Section: Model For Enhanced Disease Resistancementioning
confidence: 99%